Evaluation of cytotoxic potential, oral toxicity, genotoxicity, and mutagenicity of organic extracts of Pityrocarpa moniliformis. Issue 3 (1st February 2019) - Rocha, Tamiris Alves; Moura, Danielle Feijó de; Silva, Marllyn Marques da; dos Santos Souza, Talita Giselly; Lira, Maria Aparecida da Conceição de; Barros, Dayane de Melo; da Silva, Alexandre Gomes; Ximenes, Rafael Matos; Falcão, Emerson Peter da Silva; Chagas, Cristiano Aparecido; Júnior, Francisco Carlos Amanajás de Aguiar; Santos, Noêmia Pereira da Silva; et al.
ABSTRACT: The objective of this study was to determine the cytotoxicity of organic extracts of P. moniliformis in vitro and identify the acute toxicity and genotoxicity in vivo . The leaves were extracted using three organic solvents (cyclohexane [EP1], ethyl acetate [EP2], and methanol [EP3]). Phytochemical qualitative analysis was performed by thin layer chromatography (TLC). Cytotoxicity tests were performed on human embryonic kidney (HEK) cells and J774 murine macrophages. Acute toxicity in mice was measured after intraperitoneal (ip) administration of 2000 mg/kg, while evaluation of genotoxicity and mutagenicity were assessed using the comet assay and the micronucleus (MN) test, respectively. The TLC analysis of the extracts revealed the presence of flavonoids, triterpenes, steroids, and saponins. In the cytotoxicity assay, extracts EP1 and EP3 altered proliferation of HEK cells, and all organic extracts increased the viability of J774 cells. In the toxicity tests, no deaths or behavioral alterations were observed in mice exposed to the acute dose of the extracts. Although some extracts led to changes in hematological and histological parameters, these results did not indicate physiological changes. In relation to the MN test and comet assay, no significant changes were detected in the DNA of the animals tested with the extracts EP1, EP2, and EP3. Thus, extracts of P. moniliformis were not considered to be toxic and did not induce formation of MN or damage to cellular DNA in the genotoxicity tests.